RESTORING A STIGMATIZED TOURIST DESTINATION: COMMUNICATION STRATEGIES OF POKDARWIS SONGGOKERTO IN BATU CITY, INDONESIA - Muhammad Rizki Rinaldi; Bambang Dwi Prasetyo; Maulina Pia Wulandari (Perspektif Komunikasi Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2025)
This research investigates the communication strategies utilized by Pokdarwis Songgokerto to rehabilitate the reputation of the stigmatized Songgoriti tourist area in Batu City, Indonesia. It is based on the recognition that a destination's image strongly shapes tourist perceptions and visit choices, with negative stigmas enduring even after real improvements. Adopting a qualitative descriptive method, data were gathered via in-depth interviews, participant observation, and document review from key informants such as Pokdarwis members, local residents, tourism entrepreneurs, and officials. The results show that Songgoriti's negative reputation, primarily tied to hidden prostitution, has solidified as a socially constructed and entrenched stigma, amplified by media portrayals and communal recollections. Pokdarwis Songgokerto counters this through a community-oriented communication approach that rebuilds social interpretations via routine interactions, eschewing outright image refutation. This involves elevating hospitality, refining service standards, and crafting positive visitor encounters to stimulate natural word of mouth promotion. The research underscores communication as a social practice woven into daily routines, positioning communities as dynamic creators of emerging narratives. This method resonates with remedial strategies in image restoration theory, highlighting the roles of credibility, consistency, and communal involvement. Despite hurdles like stakeholder opposition and limited policy backing, it proves effective in progressively reshaping views. In essence, reviving a stigmatized destination's image demands sustained, experiential, and inclusive communication endeavors.